How to do a science project and report - Gutnik, Martin J. (New York : F. Watts, 1980)
Discusses performing scientific research following the eight steps of the scientific method and writing a formal report of the results following a special format.
Includes index.
Keywords: Science -- Experiments -- Juvenile literature; Report writing -- Juvenile literature; Science -- Experiments; Report writing; Experiments